Using administrative data to transform travel and tourism estimates - Mylles, Sally (International Journal of Population Data Science, 2026)
Following a review of our statistics in 2019, the UK Office for National Statistics (ONS) are transforming the way we collect travel and tourism (T&T) data to deliver more efficient, accurate and coherent estimates. The Travel and Tourism Reform Project aims to explore the use of linked administrative data in transforming the current International Passenger Survey (IPS). The Admin Data Team has been exploring administrative data that will give insight into travel and tourism inbound to and outbound from, the UK. Primarily, ONS have been exploring short-term accommodation, mobility, and financial transaction data (e.g. Airbnb, Advanced Passenger Information and Visa Card data), to better understand international mobility, transportation and patterns of spending inside and out of the UK. To date, our research has shown that there is substantial promise, and benefits, in supplementing traditional survey methods with administrative sources; this includes work conducted to match variables, compare data and produce travel and tourism statistics.